2012
DOI: 10.1111/j.1349-7006.2012.02266.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional variable number of tandem repeats variation in the promoter of proto‐oncogene PTTG1IP is associated with risk of estrogen receptor‐positive breast cancer

Abstract: Genetic polymorphisms in the signalling pathway of estrogen receptor (ER) could modify the risk of breast cancer. A variable number of tandem repeats (VNTR) polymorphism in the promoter of PTTG1IP, pituitary tumor transforming gene binding factor targeted by estrogen receptor a (ERa) in endocrine neoplasia, has been shown to be functional, but its relevance to cancer etiology was unknown. We investigated its association with breast cancer risk by genotyping in 658 patients and 866 controls and further analysed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Also, exposing breast cancer cell cultures to oestrogen has been shown to up-regulate PTTG1IP expression [ 7 ]. It has also been reported that the variable number of tandem repeats in PTTG1IP promoter might be associated with an increased risk of ER-positive breast cancer [ 15 ]. Very few previous reports have correlated the findings with the immunohistochemical expression of PTTG1IP.…”
Section: Discussionmentioning
confidence: 99%
“…Also, exposing breast cancer cell cultures to oestrogen has been shown to up-regulate PTTG1IP expression [ 7 ]. It has also been reported that the variable number of tandem repeats in PTTG1IP promoter might be associated with an increased risk of ER-positive breast cancer [ 15 ]. Very few previous reports have correlated the findings with the immunohistochemical expression of PTTG1IP.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of PBF has been circumstantially associated with metastasis in patients with breast (17) and thyroid cancer (16), and we recently reported that patients with colorectal cancer who demonstrate extramural vascular invasion have significantly higher PBF expression (18). However, these associations have not been appraised for causality, and the in vitro mechanisms by which PBF induces tumor cell invasion are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…First, high PBF expression was correlated with distant metastasis at diagnosis, tumor node metastasis (TNM) stage and disease-specific survival in a large series of papillary thyroid cancers (16). Secondly, high PBF promoter activity was associated with poorer clinical outcome and increased metastatic risk in breast cancer (17). Thirdly, colorectal tumors with higher PBF protein expression demonstrated greater vascular invasion (18).…”
mentioning
confidence: 99%
“…Although the significance of epigenetic changes in tandem repeats on lung cancer development has been repeatedly demonstrated, the initial determinants of hypomethylation are not yet well understood [Xiang et al, ]. Little research has investigated the interplay among tandem repeats methylation, inflammatory responses, and cellular oxidative stress induced by ambient PM insult.…”
Section: Introductionmentioning
confidence: 99%